Nas trilhas do romance: uma leitura literária da Donzela guerreira - Brito, Kathiuscia Santos de (2020)
This work intends to present a literary reading proposal based on the novel Donzela Guerreira, selected from the book by Jackson da Silva Lima: “O folklore em Sergipe” (1977). Novels are oral narratives sung in verse and constitute themselves as a popular oral genre. The choice of the genre is justified in view of the reduced number of reading proposals aimed at the texts of the popular oral tradition, with regard to teaching literature. Thus, among the innumerable novels, the novel Donzela Guerreira was selected. The study of the novel is based on research carried out by Alvanita Santos (2005), in her thesis entitled, Canto das Mulheres - Between dancing and working: gender relations in oral narratives (novels), together with the dissertation work. on the novels in the Sergipe context, by Antônio Marcos Trindade, entitled “The lament of Severinas: gender relations in the Sergipe novelist”. The literary reading was made from the theoretical reflections addressed by Rouxel and Rezende (2013) on subjective reading, sensitive reader training and aesthetic experience. The research was carried out in a school of the state network of Sergipe with students of the 9th year of elementary school II. When understanding the novels as texts of popular oral literature belonging to the female universe, the possibility of proposing a literary reading from a perspective of the gender relations present between the novel Donzela Guerreira, along with the short story: “Between the sword and the rose”, by Marina Colasanti (1992). This research presents as a work proposal the realization of literary reading workshops aiming, among other objectives, to enable (re)knowledge of popular oral literature, familiarize students with the literary reading of novels, in order to provide the development of experiences aesthetics unique to students, following the assumptions presented by Rouxel (2013). The research presents the “Reading Notebook: Donzela Guerreira: in search of the oral tradition of Sergipe” as a didactic material that seeks to promote to teachers and students a (re) knowledge of a genre of the popular oral tradition, aiming to guarantee the inclusion of orality in the teaching of literature and contribute to the formation of readers